Implementasi Revitalisasi Perpustakaan di SDN 1 Gelung Kabupaten Situbondo - Nani Farah Fasica; Siti Aminah; Ahmad Riyadi (GUNAVATTA : Jurnal Pengabdian Masyarakat, 2025)
The library revitalization implementation activity was carried out at SDN 1 Gelung. This community service activity was an output of the elementary school library management course. Library revitalization activities were carried out at SDN 1 Gelung, Panarukan District, Situbondo Regency. The first activity carried out by the service team was cleaning the library, then continuing with dismantling the Library book collection which did not match the type, numbering and clasification with DDC (Decimal Dewey Clasification), giving out bags and borrower cards, writing master books, making visit lists, and writing circulation of in and out Library books. This library revitalization implementation activity is carried out so that the library can be used properly as a storehouse of knowledge, and apart from that, this revitalization activity really helps the school in improving the library, its facilities and infrastructure, and library management so that it can be more effective.